Penilaian Risiko Ergonomi Pada Pekerja Tenun Tradisional di Sentra Industri Tenun - Maksuk, Maksuk -; Shobur, Sherli; Habibi, Umar (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2021)
Ergonomic risk factors for weaving workers are generally caused by repetitive work, long working period, wrong awkward work and work positions. The objective study was to assess the ergonomic risk level of weaving workers at weaving industry centers. This study was an observational study with a cross-sectional design, using the REBA methods. This study was conducted in April - September 2019 at the weaving industry center in Palembang. Ergonomics risk assessment is carried out at the stages of the weaving process starting from the yarn coloring, spinning, yarn winding, yarn insertion in the yarn rack, twisting, milling, winding the yarn after it has been rolled and the weaver.  Data were collected using REBA worksheets, observation and documentation. Furthermore, the data were analyzed based on the scores from the REBA table. The results of the ergonomics risk assessment using REBA scores at each stage of the process with the following details: in the warp yarn process the final score of 9 (high risk), the final score of 9 (high risk), handling (final score 11 = very high risk), punishment (final score 11 = very high risk), twisting (final score 9 = high risk), slashing (final score 7 = moderate risk), palletizing (final score 9 = high risk) and weaving process (final score 9 = high risk). The level of ergonomic risk for weaving workers in Palembang was moderate, high and very high risk, so it is necessary to immediately repair the equipment, especially the equipment for the weaving process.